2021
DOI: 10.1177/08927057211013070
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of cutting parameters in turning of PEEK composite using artificial neural networks and adaptive-neural fuzzy inference systems

Abstract: Polyetheretherketone (PEEK) and its composites are commonly used in the industry. Materials with PEEK are widely used in aeronautical, automotive, mechanical, medical, robotic and biomechanical applications due to superior properties, such as high-temperature work, better chemical resistance, lightweight, good absorbance of energy and high strength. To enhance the tribological and mechanical properties of unreinforced PEEK, short fibers are added to the matrix. In this study, Artificial Neural Networks (ANNs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…This allows robots to deal with diverse situations, such as passing through narrow passageways, interacting with users, or moving in unpredictable environments. It can also be used in mobile robots that must make decisions about speed and direction to reach a destination without exact knowledge of road conditions [74].…”
Section: Methodsmentioning
confidence: 99%
“…This allows robots to deal with diverse situations, such as passing through narrow passageways, interacting with users, or moving in unpredictable environments. It can also be used in mobile robots that must make decisions about speed and direction to reach a destination without exact knowledge of road conditions [74].…”
Section: Methodsmentioning
confidence: 99%
“…A wide range of advanced prediction methods (e.g. ANN [102][103][104], Fuzzy logic based model [105,106] ) and optimization techniques (e.g. Particle swarm optimization (PSO) [107], grey relational analysis and Non-dominated Sorting Genetic Algorithm-II (NSGA-II) [108] ) have been reported for optimization of cutting force [103][104][105]107,[109][110][111], surface roughness [103,106,[110][111][112][113][114], cutting power consumption [107,111,112] and specific cutting pressure [107,108]).…”
Section: Turningmentioning
confidence: 99%
“…In addition to the better mechanical and/or thermal properties, their prices are competitive, very suitable for structural parts in different fields such as automobile, medical appliances, electronics, aerospace, construction machinery, and biomechanical applications. 1,4…”
Section: Introductionmentioning
confidence: 99%
“…In general, the cutting force is the most sensitive indicator of machining performance including the tool condition and chip formation. 10 Özden et al 4 indicated that machinability of PEEK and its composites can be improved based on the cutting force induced. An appropriate cutting force during machining results in less tool wear and better dimensional accuracy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation